As representações ideológicas nas vozes polifônicas das personagens de Incidente em Antares, de Érico Verissimo - Fanchin, Leandro (My University, 2014)
This dissertation examines the ideological representations present in the voices of the characters in the novel Incidente em Antares, by Erico Verissimo, with the support of the theory of Mikhail Bakhtin, especially his concept of polyphony. It attempts to demonstrate that this novel, published in 1971, is a polyphonic novel, in which multiple voices are heard with their total intensity, enabling the representation of different ideologies and worldviews, inserted into a clipping of the socio-historical context of the fictional universe of the narrative. The emphasis on the historical novel approach defines the study as interdisciplinary, because it focuses on the relation between literature and history, priorizing the period immediately before and after the 1964 military coup, and the context of production of the work. The voices of the characters that will be analyzed belong to different segments and classes as decadent landowners, representatives of authoritarian law, liberals and those who fight against all forms of authoritarianism, excluded by the socio-economic system, the different sectors of the Catholic Church and the press. This study also presents the characters of the novel as regional voices through the characteristics of regionality that configure identities in the fictitious city of Antares.
Esta dissertação examina as representações ideológicas presentes nas vozes das personagens do romance Incidente em Antares, de Erico Verissimo, com o auxílio da teoria de Mikhail Bakhtin, especialmente, o seu conceito de polifonia. Busca-se demonstrar que esse romance, publicado em 1971, é um romance polifônico, no qual várias vozes se fazem ouvir com plenivalência, possibilitando a representação de diferentes ideologias e visões de mundo, inseridas em um contexto sócio-histórico recortado no universo ficcional da narrativa. A ênfase dada à abordagem histórica do romance define o estudo como interdisciplinar, pois que enfoca a relação entre literatura e história, priorizando-se o período imediatamente pré-e pós-golpe militar de 1964, além do contexto de produção da obra. As vozes das personagens que serão analisadas pertencem a diferentes segmentos e classes sociais, como: os latifundiários decadentes, os representantes autoritários da lei, os liberais e os que lutam contra toda forma de autoritarismo, os excluídos pelo sistema socioeconômico, os diferentes setores da Igreja Católica e a imprensa. Esse estudo também apresenta as personagens do romance como vozes regionais por meio das características de regionalidade que configuram identidades na fictícia cidade de Antares.
Keywords: Veríssimo, Érico; Incidente em Antares (Obra literária); Literatura sul-rio-grandense